Influence of Intercropping Arisaema amurense with Acanthopanax senticosus on Soil Microbial Community and the Effective Ingredients of A. senticosus - Jiapeng Zhu; Yayu Zhang; Cai Shao; Bochen Lv; Hao Liang; Weiyu Cao; Guojia Zhang; Hai Sun (Horticulturae, 2024)
Intercropping is an effective cultivation strategy for promoting soil health, changing microbial community, reducing fertiliser application and enhancing the quality of medicinal plants. Nevertheless, the interaction effect of intercropping between Arisaema amurense and Acanthopanax senticosus remains unknown. Herein, we investigated the difference in soil properties, soil enzyme activities, microbial community diversity and active ingredients of A. senticosus in monoculturing versus intercropping of A. senticosus/A. amurense in a field experiment. High-throughput sequencing and liquid chromatography–mass spectrometry were employed to explore the growth promotion effect in the intercropping mode. Results revealed that intercropping benefitted the accumulation of ammonium nitrogen and total nitrogen in soil; total nitrogen and ammonium nitrogen increased by 33% (rhizosphere) and 65% (inter-row) and by 123% (rhizosphere) and 124% (inter-row) at 0–20 cm soil depths, respectively. Furthermore, intercropping increased the soil carbon/nitrogen ratio at the soil from 20 to 40 cm and promoted the growth of the root system of the deep-rooted plant A. senticosus. However, it exerted a certain inhibitory effect on the activities of urease, sucrase and neutral phosphatase on the soil surface. Intercropping increased bacterial diversity and inhibited fungal diversity in soil, potentially preventing the soil microflora changed from bacterial type to fungal type. In terms of community composition, intercropping exhibited a greater effect on bacteria than on fungi. At the phylum level, the relative abundance of microorganisms associated with nutrient cycling and increased ecosystem resistance increased in intercropped soils, such as those of Proteobacteria, Actinobacteriota and Bacteroidota. At the genus level, the bacterial genera that showed significantly increased relative abundance in intercropping soil included unclassified_Acidobacteriales, Sphingomonas, Gemmatimonas and Candidatus_Solibacter. Furthermore, the relative abundance of Cladosporium, a potential plant pathogen in intercropped rhizosphere soil, was 42% lower than that in monocultured rhizosphere soil. Additionally, intercropping can promote the accumulation of eleutheroside B, eleutheroside E, quercetin, protocatechuic acid and polysaccharide, which increased by 551%, 53%, 10%, 28% and 26%, respectively, compared with that after monoculturing. According to the Pearson correlation heat map, rapidly available phosphorus, rapidly available potassium, ammonium nitrogen, nitrate nitrogen, total nitrogen and urease exhibited the greatest impact on the soil microbial community and on the active ingredients of A. senticosus. In conclusion, intercropping altered the composition of the soil microbial community and increased the content of the active ingredients of A. senticosus, consequently begetting economic and ecological benefits.